Successful Total En Bloc Spondylectomy of T7 Vertebra for Hepatocellular Carcinoma Metastasis After Living Donor Liver Transplantation. Issue 16 (15th August 2015) - Kimura, Hiroaki; Fujibayashi, Shunsuke; Shimizu, Takayoshi; Otsuki, Bungo; Murakami, Hideki; Kaido, Toshimi; Uemoto, Shinji; Matsuda, Shuichi
<x xml:space="preserve">Abstract</x> Study Design. Case report. Objective. We report a patient who was successfully treated with total en bloc spondylectomy (TES) for T7 metastasis after living donor liver transplantation for hepatocellular carcinoma (HCC). Summary of Background Data. Spinal metastasis from HCC has a poor prognosis. There are only a few studies on surgical outcomes of spinal metastasis from HCC. Because of the high surgical morbidity and short life expectancy in patients with HCC with spinal metastasis, TES is not considered in these patients, although several studies have reported satisfactory results for TES for some types of metastatic spinal tumors. Liver transplantation (LT) is the curative treatment option for early HCC. However, the recurrence of HCC is a possible problem after LT, although no reports on surgery for spinal metastasis following LT for HCC have been published. We report on the first case of a patient who was successfully treated with TES for T7 metastasis after living donor LT for HCC. Methods. The patient was a 65-year-old man, who had undergone living donor LT for HCC 2 years before. His main symptom was progressive gait disturbance because of the spinal cord compression by the tumor at T7. Radiology and pathology examinations revealed a solitary metastasis at T7 with neither recurrence in the liver nor metastasis in the other organs. We performed TES using a pedicle screw system and a mesh cage filled with frozen autografts. Results. After surgery, the patient showed clear improvement in neurological symptoms. At 3 months after surgery, a T4 metastasis was detected with magnetic resonance imaging, and the patient was treated with heavy ion radiotherapy. He could walk without a cane and there was no evidence of recurrence at 1.5 years after surgery. Conclusions. Solitary spinal metastasis of HCC may become an indication for TES if liver function improves after LT. Level of Evidence: 5